Monoclonal antibodies to human leucocyte antigens in polymyositis and muscular dystrophy. - Rowe, D; Isenberg, D; Beverley, P (1983)
Biopsy specimens from patients with treated or untreated polymyositis and muscular dystrophy controls were examined by indirect immunoperoxidase staining with a panel of monoclonal antibodies to human leucocyte antigens. In untreated polymyositis, helper/inducer T cells were the predominant T cell subset. In treated cases few T cells were seen. Overall, few T cells were seen in dystrophic cases, most infiltrating cells being dendritic and lacking T cell antigens. Staining of sarcolemma with anti-HLA class 1 antibody is weak or negative except in areas adjacent to infiltrating leucocytes or where muscle fibre damage is apparent.